Macro/micro porous silk fibroin scaffolds obtained via combined methodologies for articular cartilage and meniscus tissue engineering - Yan, Leping (2011)
This study proved that the salt leached silk fibroin scaffolds can be developed by using more than 10 wt% aqueous silk fibroin solutions. There were some previous studies shown that this was impossible.